Estudio de los procesos de corrosion de una aleacion metalica de cobre usada en odontologia - Guastaldi, A. C.; Sobreira, C. R.; Vaz, Luis Geraldo [UNESP] (My University, 1997)
Corrosion phenomena in a dental copper-based alloy are experimentally studied using electrochemical techniques. Two heating sources, torch and induction, were used in the casting experiments. In the corrosion essays, the optimum casting cycle and the polarization curves were obtained. It was found that the heating sources have little influence on the corrosion processes of the metallic alloys studied.
Study of corrosion processes in a dental copper-based alloy
Keywords: Copper alloys; Electrochemical corrosion; Induction heating; Metal casting; Polarization; Copper based dental alloys; Dental alloys